Making the Student Experience Everybody's Business : Cultivating Collaboration in the Exosphere. - Bridge, Christopher; Horey, Dell; Julien, Brianna; Thompson, Belinda; Loch, Birgit (Student Success v.15 n.2 p.34-44 https://doi.org/10.5204/ssj.3434, 2024)
It has long been recognised that a key element in improving student transition, retention and success in higher education is cross-institutional consistency and unity of action among disparate academic, policy and support units. However, transferring this principle into practice often requires overcoming departmental silos, negotiating shared understandings of key concepts, and establishing patterns of cross-institutional collaboration in spaces where this may have been lacking. This study examines the effect of a program of supported communities of practice among teaching academics that sought to improve the culture of learning and teaching in a large science, health and engineering faculty in an Australian university. We found indications that these communities of practice promoted collaboration by functioning as loci of cross-institutional consultation and coordination, providing the basis for an enhanced student experience. We interpret this finding through the lens of Bronfenbrenner's ecological model of development, and propose an approach based on academic communities of practice as a way of building cross-institutional unity of action and making the student experience everybody's business. [Author abstract]